Relato digital en la enseñanza de español: mediación sociocultural y formación de la identidad personal - Llopis i Alarcón, Moisés (Colombian Applied Linguistics Journal, 2025)
This article explores the teaching of Spanish as an additional language (SAL) from a sociocultural perspective, emphasizing the importance of mediation, awareness, and creativity in the educational process. These dimensions are fundamental for reframing teaching as a practice that goes beyond the transmission of linguistic knowledge to foster the co-construction of learners’ personal identities. Employing an action research methodology, the study integrates digital storytelling as a pedagogical tool to support sociocultural mediation and identity formation. It examines the experiences of adult learners at a Chilean university, offering insight into the effective use of digital narratives in language education. Through personal storytelling and digital creation, students actively shape their identities within an interactive and reflective learning environment. The findings highlight improvements in linguistic competence, alongside a strengthened emotional and cultural engagement with the Spanish language.